2007
DOI: 10.1137/s0097539705447372
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Inapproximability Results for MAX‐CUT and Other 2‐Variable CSPs?

Abstract: In this paper we show a reduction from the Unique Games problem to the problem of approximating MAX-CUT to within a factor of α GW + ∈, for all ∈ > 0; here α GW ≈ .878567 denotes the approximation ratio achieved by the Goemans-Williamson algorithm [26]. This implies that if the Unique Games Conjecture of Khot [37] holds then the Goemans-Williamson approximation algorithm is optimal. Our result indicates that the geometric nature of the Goemans-Williamson algorithm might be intrinsic to the MAX-CUT problem.Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
416
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 424 publications
(427 citation statements)
references
References 49 publications
10
416
0
Order By: Relevance
“…The Original Conjectures. We note again that our results do not contradict the precise conjectures stated in [17,15] as these are stated in the case where the measures of all partition elements are exactly 1/k. However, the authors of [17,15] gave no indication that they believe there is something special about the case of equal measured partitions -rather, they made the conjectures that were needed for the applications presented in their paper.…”
Section: 1supporting
confidence: 63%
See 2 more Smart Citations
“…The Original Conjectures. We note again that our results do not contradict the precise conjectures stated in [17,15] as these are stated in the case where the measures of all partition elements are exactly 1/k. However, the authors of [17,15] gave no indication that they believe there is something special about the case of equal measured partitions -rather, they made the conjectures that were needed for the applications presented in their paper.…”
Section: 1supporting
confidence: 63%
“…Furthermore it was shown in [15] that the standard simplex being optimal for Gaussian noise stability is equivalent to the fact that plurality is stablest. Therefore, the authors of [17,15] conjectured that plurality is stablest and demonstrated a number of applications of this result in hardness of approximation and voting.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Since, assuming the Unique Games Conjecture (UGC for short) of Khot [15], it is NP-hard to approximate Max-2Lin-2 beyond a factor of 0.878 [16], the same bound holds under UGC for Max-PGI k and Max-EGI k by the same reduction. Since Max-PGI k and Max-EGI k are easily seen to be instances of generalized 2CSP, they have constant factor approximation algorithms, for a constant factor depending on k. In fact, it turns out that Max-EGI 2 and Max-PGI 2 are tightly classified by Max-2Lin-2 with almost matching upper and lower bounds (details are given in Section 2).…”
Section: Introductionmentioning
confidence: 99%
“…We prove the following theorem by giving a factor-preserving reduction from Max-2Lin-2 (e.g. see [16]) to Max-PGI k and Max-EGI k .…”
Section: Introductionmentioning
confidence: 99%